Ta‘zῑz Al-Qayyim al-Akhlāqiyyah Bi Istirātijiyyah Al-Tawāṣul Asnā’a Ta‘lῑm Al-Lugah Al-‘Arabiyyah Fi ‘Asr Al-Ta‘allumi Al-Mustaqilli Bi Ma‘had Dāru as-Salām Jombang - Lailatul Qomariyah; Akhmad Sauqi Ahya; Faishol Mahmud Adam Ibrahim (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2022)
The aim of this study is to describe the speaking strategies in strengthening character values at learning arabic at the independent learning’s era in Darus Salam Islamic Boarding School.This research was designed with a qualitative approach, with the type of case study. A method for collecting data by observations in teaching Arabic language, and documenting the teacher's speech act’s strategy, and interviewing the context of these teacher’s actsand is analyzed by interactive model analysis. The results of this research are, strengthening character values by the communication strategy with two strategies: A) the direct strategy with five functions, 1) the request, 2) the command, 3) the invitation, 4) The hope, 5) The advice; b) the indirect strategy has two functions, 1) The request, and 2) The command. The results of this study contribute to the teacher's communication strategy in using appropriate verbal verbs as an attempt to build students who have a moral character and become more interactive and communicative learning while teaching Arabic. Therefore, it is necessary to conduct the following research to understand moral values through the educational materials for writing skill that include moral values in them in Arabic learning. Keywords: Character Value, Independent Learning, Speaking Strategies Abstrak Penelitian ini bertujuan untuk mendeskripsikan strategi bertutur dalam penguatan nilai karakter Pada pembelajaran Bahasa Arab di Pondok Pesantren Darus Salam Jombang di era Merdeka Belajar. Penelitian ini dirancang dengan pendekatan kualitatif, dengan jenis studi kasus. Metode pengumpulan data dengan observasi pembelajaran bahasa Arab, dan mendokumentasikan strategi tindak tuturnya, dan mewawancarai kontekstersebut dan Kemudian dianalisis dengan analisis model interaktif. Hasil penelitian ini adalah, penguatan nilai karakter melalui strategi bertutur dengan dua strategi: A) strategi langsung dengan enam fungsi, 1) permintaan, 2) perintah, 3) ajakan, 4) Harapan, 5 ) Nasihat; b) strategi tidak langsung memiliki dua fungsi, 1) Permintaan, 2) Perintah. Hasil penelitian ini berkontribusi pada strategi bertutur guru dalam menggunakan tindak tutur yang tepat sebagai upaya untuk membentuk siswa yang memiliki nilai karakter dan menjadi pembelajaran yang lebih interaktif dan komunikatif. Oleh karena itu, perlu dilakukan penelitian berikut untuk memahami nilai-nilai karakter melalui materi pendidikan keterampilan menulis yang memuat nilai-nilai karakter di dalamnya pembelajaran bahasa Arab. Kata kunci: Nilai Karakter, Merdeka Belajar, Strategi Bertutur